2022
DOI: 10.1111/eea.13140
|View full text |Cite
|
Sign up to set email alerts
|

Phoretic specialization on insect herbivores facilitates mite transportation to host plants

Abstract: Phoresy, the use of another organism for dispersal, is one of the most intriguing commensalistic interactions. The selection of a correct host is fundamental for phoretic organisms to ensure arrival to suitable habitats and to encounter potential mates. This study focuses on a group of phoretic mites in the genus Lasioseius (Acari: Blattisociidae).In La Selva Biological Station, a tropical wet forest in Costa Rica, Lasioseius mites feed on nematodes inside the scrolls formed by the young leaves of their hosts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For instance, mites of the genus Lasioseius who feed on nematodes inside leaf scrolls of Zingiberales plants require phoretic assistance for their dispersal by rolled‐leaf beetles. Bizzarri et al (2022) revealed an interesting olfactory mechanism underlying this specific occurrence of phoresy. They determined that the mites are specifically attracted to scents of rolled‐leaf beetle species sharing the same Zingerales host plants with them, but not to the scent of another rolled‐leaf beetle species occurring on Zingerales plants where the mites do not naturally feed.…”
mentioning
confidence: 98%
“…For instance, mites of the genus Lasioseius who feed on nematodes inside leaf scrolls of Zingiberales plants require phoretic assistance for their dispersal by rolled‐leaf beetles. Bizzarri et al (2022) revealed an interesting olfactory mechanism underlying this specific occurrence of phoresy. They determined that the mites are specifically attracted to scents of rolled‐leaf beetle species sharing the same Zingerales host plants with them, but not to the scent of another rolled‐leaf beetle species occurring on Zingerales plants where the mites do not naturally feed.…”
mentioning
confidence: 98%